Interferon Beta treatment in neuromyelitis optica: increase in relapses and aquaporin 4 antibody titers. - Palace, J; Leite, M; Nairne, A; Vincent, A (2010)
OBJECTIVE: To describe a patient with neuromyelitis optica (NMO) whose aquaporin 4 (AQP4) antibody levels increased following treatment with interferon beta. DESIGN: Prospective clinical and laboratory case report. SETTING: Institutional referral center for multiple sclerosis (MS). Patient One patient with an initial diagnosis of MS that was later revised to NMO. INTERVENTIONS: A course of interferon beta-1a followed by conventional immunosuppression. Blood samples were collected from the onset of treatment, and clinical and laboratory assessment was performed. MAIN OUTCOME MEASURES: Serum levels of AQP4 antibody and number and characteristics of neurological relapses. RESULTS: After 3 relapses during a 10-month period despite interferon beta-1a treatment, the diagnosis of AQP4 antibody-positive NMO was made and treatment was switched to prednisolone and methotrexate. The AQP4 antibody titers rose dramatically during treatment with interferon beta, and then fell when conventional immunosuppressive therapy was substituted; the patient has remained relapse-free for the subsequent years. CONCLUSIONS: Although previous articles have suggested that interferon beta may increase relapses in NMO, this is the first to illustrate an increase in AQP4 antibodies associated with such treatment.